If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1y = y Solving 5 + -1y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 5 + -1y + -1y = y + -1y Combine like terms: -1y + -1y = -2y 5 + -2y = y + -1y Combine like terms: y + -1y = 0 5 + -2y = 0 Add '-5' to each side of the equation. 5 + -5 + -2y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2y = 0 + -5 -2y = 0 + -5 Combine like terms: 0 + -5 = -5 -2y = -5 Divide each side by '-2'. y = 2.5 Simplifying y = 2.5
| 5y-18=8y | | y+46=3y | | 173-7x=29x+17 | | 11-7x=33-14x | | -87-7x=10+15 | | (2x+1)(3x-2)=0 | | 10x^2-29+10=0 | | 57=14x+3y | | 14x+3y=57 | | 4x-(3x+4)=3 | | (33*19-1)-8(4*19+3)= | | (33-25-1)-8(4-25+3)= | | (33b-1)-8(4b+3)=-6 | | x(x+2)(x^2-1)=-1 | | p=-5x^2+100x | | 16+x=24 | | 8t+3(1-5t)= | | n*2+3=28 | | 7+4n=19 | | 3x^2+6x=2x^2-9 | | .25q+.10d=14.05 | | 7x^2=15x+x^2 | | (x+8)(x+5)=(3x-5)(x-8) | | x^2=12-x | | 44=w(2w+3) | | 4x^2+15x+4=22 | | 4x+15=22 | | 17y-3=87-y | | N=0.05x-99.05 | | -9(t-8)-(t+7)=1 | | 4x+1=5x-25 | | X^3-3X-9X-27=0 |